Features of the clinical course of comorbid gastroesophageal reflux disease and chronic gastroduodenitis in children - N.V. Kirianchuk (Zaslavsky O.Yu., 2018)
Background. The incidence of gastroesophageal reflux disease (GERD) in children varies from 2-4 to 9-49 % according to different authors, and comorbid lesions of the upper digestive tract - from 15 to 38 %. The improvement of non-invasive diagnosis of these conditions in children is relevant. To study the clinical features of GERD and chronic gastroduodenitis (CGD) in children was the purpose of our study. Materials and methods. We have examined 71 patients aged from 10 to 18 years. Group I included 33 children with comorbid GERD and chronic gastroduodenitis, group II consisted of 16 individuals with GERD, and group III - of 22 children with chronic gastroduodenitis. Diagnoses of GERD and chronic gastroduodenitis were made according to International Classification of Diseases, 10th revision, on the basis of the complaints and medical histories, as well as objective examination, and verified by endoscopic examination. Analysis of the obtained results was performed using non-parametric methods of chi-square test and Fisher's exact test. Results. We compared the incidence of the main clinical symptoms in the study groups. The incidence of heartburn, sour taste in the mouth, nausea was not statistically different in children of different groups. The incidence of abdominal pain was not different in groups with comorbid GERD and CGD, but it was significantly less common in children with GERD. It was also found that non-esophageal symptoms (pathological changes of the tongue, carious teeth, signs of chronic pharyngitis, cardialgia, palpitations) were significantly more common in children with comorbid GERD and chronic gastroduodenitis compared with a group of children with CGD. Conclusions. The obtained results can be used to develop algorithms for the diagnosis of comorbid GERD and CGD.